The impact of patient-reported factors of endoscopic screening experience on attendance at future examinations and distal colorectal cancer incidence - Sharon Power; Kate Wooldrage; Siwan Thomas-Gibson; Amanda J. Cross (BMC Cancer)
Abstract Background Endoscopic examinations can reduce colorectal cancer (CRC) burden through early detection and removal of precancerous lesions; however, after initial endoscopy, some patients do not attend subsequent examinations. Aims To investigate the impact of patient experience of endoscopic screening on attendance at future examinations and distal CRC incidence. Methods In a cohort study including 40,141 participants who received flexible sigmoidoscopy (FS) screening in the UK FS Screening Trial, median follow-up was 16.8 years. We examined family history of CRC, bowel preparation quality, segment of bowel reached, and responses to patient-reported post-examination questionnaires. We estimated multivariable odds ratios (OR) for attendance at future examinations by logistic regression and hazard ratios (HR) for associations between patient experience at FS and distal CRC incidence. Results Of those recommended a future endoscopy, 7.1% did not attend repeat FS, 3.4% did not attend colonoscopy, 18.3% did not attend surveillance, and 0.5% developed distal CRC. Symptoms of faintness/dizziness (OR = 5.10 95%CI 1.49–17.42) were associated with non-attendance at repeat FS. Non-attendance at surveillance was associated with whether participants felt they had made the right decision to take the tests; that taking the tests was tempting fate; that they needed the tests; or that they would rather have let nature take its course. A FS more painful than expected (HR = 0.57 95%CI 0.37–0.88) was inversely associated with distal CRC incidence. Conclusions We identified aspects of patient experience at endoscopy that could be used to improve attendance at future endoscopic examinations, which in turn could reduce CRC incidence. Trial registration number: ISRCTN28352761. Trial registration date: April 2000.